Assessment of along-normal uncertainties for application to terrestrial laser scanning surveys of engineering structures. Issue 364 (2nd January 2019) - Mill, Tarvo; Ellmann, Artu
Abstract : A method for estimating the range and spatial distribution of terrestrial laser scanning uncertainties occurring during the survey of engineering structures is presented and numerically verified. The emphasis is on the assessment of along-normal uncertainties of the surface to be surveyed. To investigate the behaviour of such uncertainties, various surveying scenarios are simulated and studied. Theoretical derivations are numerically verified, and these results are compared with those of previous empirical studies. The influence of along-normal noise on geometric modelling of surveyed surfaces is studied. In addition, suggestions are provided for how to optimising scanning locations, yielding the reduced ANU.